Short-term effects of air pollutants on outpatients with psoriasis in a Chinese city with a subtropical monsoon climate - Wang, Ting; Xia, Yuanrui; Zhang, Xinhong; Qiao, Nini; Ke, Susu; Fang, Quan; Ye, Dongqing; Fan, Yinguang (Frontiers in Public Health, 2022)
Psoriasis is a common skin disease that seriously affects patients’ quality of life. The association of air pollutants with psoriasis, and the extent of their effects, remain unclear. Based on a distribution lag nonlinear model, this study explored the short–term effects of air pollutants on outpatients with psoriasis in Hefei, China between 2015 and 2019 by analyzing the exposure–lag–response relationship after controlling for confounding influences such as meteorological factors, long–term trends, day–of–the–week, and holidays. Stratified analyses were performed for patients of different ages and genders. The maximum relative risks of psoriasis outpatients’ exposure to SO2, NO2, and O3 were 1.023 (95% confidence intervals (CI): 1.004–1.043), 1.170 (95% CI: 1.046–1.307), and 1.059 (95% CI: 1.030–1.090), respectively. An increase of 10 μg/m3 NO2 was associated with a 2.1% (95% CI: 0.7%–3.5%) increase in outpatients with psoriasis, and a decrease of 10 μg/m3 O3 was associated with an 0.8% (95% CI: 0.4%–1.2%) increase in outpatients with psoriasis. Stratified analyses showed that males were more sensitive to the change in meteorological factors, while females and outpatients with psoriasis aged 0–17 years old were more sensitive to the change in air pollutants. Short–term air pollutant exposures were associated with outpatients having psoriasis, suggesting that patients and high–risk people with psoriasis should reduce their time spent outside and improve their skin protection gear when air quality is poor.